Studies on Complexes of 2-(4-Aminophenyl) Benzimidazole with Zn(II), Cd(II) and Hg(II) Salts - Rekha, S.; Nagasundara, K.R. (Asian Journal of Chemistry, 2010)
Complexes of 2-(4-aminophenyl) benzimidazole with Zn(Il), Cd(Il) and Hg(II) chlorides and Cd(II) and Hg(Il) bromides have been synthesized. They have been characterized by elemental analysis, conductivity measurements, IR and 1H NMR spectral studies. The results show that the complexes are non-electrolytes, four coordinated and the ligand acts as a monodentate.